THE COMMON AGRICULTURAL POLICY THROUGH REFORMS TOWARD EUROPE 2020 - Puzić, Goran; Klevernić, Aleksandar; Pavlović, Zoran (Economics of Agriculture, 2014)
At the start of the European integration process, although the focus was on the European Coal and Steel Community, the specifc treatment of agriculture was well-known information. Often, the agricultural sector was the decisive factor in the dynamics and intensity of the integration process as a whole. That role of agriculture is maintained, but in a lot of changed conditions and with different strategy that includes the development of new targets and mechanisms. The Common Agricultural Policy (CAP) has more than 50 years one of the most expensive and the most intriguing of all EU policies. It, beside regional policy, is a key policy and many aspects of other policies of EU are diffracted on this topic. The aim of this research is the intersection of the previous reforms of the CAP until the Agenda "Europe 2020" and influence on the agricultural income and direct payments on selected countries – Bulgaria, Romania and Croatia. During research, we have used the methods of economic and political analysis and comparative-historical and current structural and dynamic context of the EU.